Evidence for multiple maternal lineages of the invasive pest Helicoverpa armigera in Argentina - Balbi, Emilia Ines; Tosto, Daniela Sandra; Flores, Fernando Miguel; Arneodo Larochette, Joel Demian (Springer, 2020)
The polyphagous Helicoverpa armigera (Lepidoptera: Noctuidae) causes significant agricultural losses worldwide. This pest has recently expanded its range into South America. Since its first report in north-western Argentina, H. armigera has already been detected in geographically distant locations within the country. In this work, mitochondrial cytochrome c oxidase subunit I (COI) and cytochrome b (Cytb) sequences obtained from H. armigera individuals collected in central and northern Argentina were analyzed to explore genetic variability. Five COI haplotypes and three Cytb haplotypes were detected among ten sequenced specimens (seven haplotypes if considering concatenated sequences). Thus, even with a limited number of samples, a high number of haplotypes was found, suggesting the occurrence of several female founder lineages of H. armigera in the country. With one exception, these mtDNA haplotypes were shared with H. armigera specimens from the neighboring countries of Brazil, Paraguay and/or Uruguay. However, the impact of natural migration and intercontinental agricultural trade on the establishment and spread of H. armigera in Argentina and other Latin-American countries is still a matter of research.